2022
DOI: 10.3389/fcvm.2022.873829
|View full text |Cite|
|
Sign up to set email alerts
|

Research on the Mechanism and Prevention of Hypertension Caused by Apatinib Through the RhoA/ROCK Signaling Pathway in a Mouse Model of Gastric Cancer

Abstract: Hypertension is one of the main adverse effects of antiangiogenic tumor drugs and thus limits their application. The mechanism of hypertension caused by tyrosine kinase inhibitors (TKIs) targeting vascular endothelial growth factors is mainly related to inhibition of the nitric oxide (NO) pathway and activation of the endothelin pathway, as well as vascular rarefaction and increased salt sensitivity; consequently, prevention and treatment differ for this type of hypertension compared with primary hypertension.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…18 The possible reason would be that apatinib might modulate vascular remodeling, nitric oxide production, endothelial dysfunction, and so on to induce hypertension in patients with recurrent PROC. 30,31 Apart from hypertension, the occurrence rate of other adverse events was not different between the two groups; which was in line with previous studies. 12,14,18 Moreover, this study discovered that the most frequent adverse events of apatinib plus chemotherapy were neutropenia (56.9%), leukopenia (47.1%), nausea and vomiting (37.3%), anorexia (35.3%), and fatigue (33.3%); meanwhile, grade 3-4 adverse events rarely occurred in patients with recurrent PROC receiving apatinib plus chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18 The possible reason would be that apatinib might modulate vascular remodeling, nitric oxide production, endothelial dysfunction, and so on to induce hypertension in patients with recurrent PROC. 30,31 Apart from hypertension, the occurrence rate of other adverse events was not different between the two groups; which was in line with previous studies. 12,14,18 Moreover, this study discovered that the most frequent adverse events of apatinib plus chemotherapy were neutropenia (56.9%), leukopenia (47.1%), nausea and vomiting (37.3%), anorexia (35.3%), and fatigue (33.3%); meanwhile, grade 3-4 adverse events rarely occurred in patients with recurrent PROC receiving apatinib plus chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, this study discovered that the incidence of hypertension was increased in patients with recurrent PROC receiving apatinib plus chemotherapy compared with patients receiving chemotherapy, which was in accordance with a previous study 18 . The possible reason would be that apatinib might modulate vascular remodeling, nitric oxide production, endothelial dysfunction, and so on to induce hypertension in patients with recurrent PROC 30,31 . Apart from hypertension, the occurrence rate of other adverse events was not different between the two groups; which was in line with previous studies 12,14,18 .…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, in animal experiments, microvascular abnormalities occur early in the development of hypertension in SHRs (Antonios et al, 2003). In addition, the latest results from our research indicated that the administration of the ROCK inhibitor Y27632 can prevent microvascular rarefaction caused by apatinib and improve blood pressure (Wang et al, 2022a). Thus, microvascular growth disorders may have given rise to a new paradigm of hypertension treatment aimed at restoring microvascular development and branching, thereby further reducing peripheral resistance and improving the structural reduction of arterial blood pressure.…”
Section: Mechanisms Of Microcirculation Damage Leading To Hypertensionmentioning
confidence: 55%
“…The typical serious adverse reaction is upper gastrointestinal bleeding 2,3 . Apatinib caused hypertension in a gastric cancer mouse model through the RhoA/ROCK signaling pathway 4 . It was reported that apatinib inhibits the proliferation of gastric cancer cells via the AKT/GSK signaling pathway in vivo 5 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Apatinib caused hypertension in a gastric cancer mouse model through the RhoA/ROCK signaling pathway. 4 It was reported that apatinib inhibits the proliferation of gastric cancer cells via the AKT/GSK signaling pathway in vivo. 5 Moreover, apatinib induced apoptosis and autophagy via AKT/mTOR pathway in anaplastic thyroid carcinoma (ATC) cell lines.…”
mentioning
confidence: 99%